Visual and circadian regulation of Drosophila BDBT and BDBT effects on DBT and PER localization - Richard Brent Nolan; Colleen Bontrager; Abigail Bowser; Alyssa Corley; Hana Fiedler; Connor Flathers; Lauren Francis; Angel Le; Seyyed Mahmoudjafari; Tinh Nim; Connor E. Muolo; Brianna Shores; et al. (iScience, 2023)
Summary: BRIDE OF DOUBLETIME (BDBT) interacts with the circadian kinase DOUBLETIME (DBT) and accumulates in eye foci during the dark of a light:dark cycle. BDBT foci are shown here to be broadly expressed in constant dark and low in constant light. Analysis of circadian photoreceptor cry and visual photoreceptor ninaE mutants showed that disappearance of eye BDBT foci requires both the CRYPTOCHROME and the RHODOPSIN-1 pathways. The arr1 and arr2 mutants, which affect rhodopsin quenching, eliminated BDBT foci under dark conditions. arr1 and arr2 mutants also caused increased nuclear PER protein. The changes in BDBT foci do not result from altered BDBT levels in the eye but from changes in its immunodetection. Knockdown of BDBT specifically in the eye produced constitutively nuclear PER and constitutively cytosolic DBT. The results show that BDBT is necessary for co-transport of DBT and PER into the nucleus and suggest that this process is regulated by a light-dependent mechanism.